Optimización de Estatores para Motores Superconductores de Flujo Axial - González Parada, Adrián; Guzmán Cabrera, Rafael; Gómez Martínez, Miguel Ángel; Ibarra-Manzano, Oscar Gerardo; Gordillo Sosa, José Antonio (Acta Universitaria, 2009)
The development of superconducting electrical machines has been designed primarily to design and build engines with the superconducting magnetic field in radial configuration, as traditional engines, so the design and construction of rotating electrical machines in axial flow configuration has become an alternative for the design and construction of such engines. In this paper we present preliminary calculations for the optimization of the stator of a superconducting motor in axial flow confi guration, based on the equations of general power of the rotary axial flow configuration. It performs the construction, optimization and evaluation of models of stators in geometries of 4, 6 and 8 poles with high-temperature superconducting tapes of Bismuth. The results show the feasibility of the design implemented, which is verified by a significant decrease in the current of superconducting motor operation.
Keywords: Array; Array; Array; Array